A hydrolytically stable europium–organic framework for the selective detection of radioactive Th4+ in aqueous solution. Issue 22 (20th May 2019) - Song, Liping; Liu, Wei; Wang, Yanlong; Chen, Lanhua; Wang, Xiao-Feng; Wang, Shuao
Abstract : Thorium is not only a promising candidate for developing next generation nuclear fuel but also a potential radioactive contaminant. Abstract : Thorium is not only a promising candidate for developing next generation nuclear fuel but also a potential radioactive contaminant. Efficient detection of thorium contamination is critically important in both nuclear science and environmental protection. We present here a 3D luminescent europium organic framework [Eu2 (FDC)3 (DMA)2 ]·4H2 O (compound1 ), which exhibits excellent hydrolytic stability and features highly selective detection capacity ( K SV = 6.68 × 10 4 ) towards radioactive Th 4+ ions among the selected monovalent, divalent and tervalent metal ions in aqueous solution. The detection limit of the material towards Th 4+ is 3.49 × 10 −5 mol L −1 which is close to the WHO standard. The detection capability and the sensing mechanism were demonstrated by Th 4+ uptake kinetics, energy-dispersive spectroscopy mapping, absorption spectroscopy, luminescence lifetime, and competitive adsorption measurements. Compound1 represents a rare case of a MOF based Th 4+ probe.